Prevalence and predictors anaemia among women of reproductive age in West Bengal, India: A cross-sectional study - Kaushalendra Prakash Goswami; Sumit Ram (National Geographical Journal of India, 2023)
Anaemia in women of reproductive age (WRA) can adversely affect maternal health and birth outcomes. Despite numerous policies and initiatives, anaemia among women continues to be a significant public health issue in India with West Bengal (WB) on the top. In order to establish priorities for public health policy, this study attempts to examine the factors associated with anaemia among WRA in West Bengal. Data was drawn from the National Family and Health Survey-5, 2019-21. A cross-sectional sample of 21408 women aged 15-49 years was analysed. Cross-tabulation was used to compute the prevalence of anaemia by background characteristics of women and Chi-squared test to check the bivariate association. Furthermore, binary logistic regression model was run to examine the contribution of the predictor variables on anaemia. Seven out of ten women in West Bengal were found anaemic. Women aged 40-49 years (Odds Ratio: 1.27, 95% Confidence Interval: 1.12-1.44, SC (OR: 1.24, 95% CI: 1.13-1.36), ST (OR: 1.72, 95% CI: 1.47-2.02), and Rural women (OR 1.26, 95% CI: 1.15-1.38); those who had no formal education (OR: 1.12, 95% CI: 0.92-1.28), belonged to the poorest households were (OR 1.34, 95% CI: 1.27-1.43), used groundwater for drinking (OR 1.13, 95% CI: 1.04-1.22), were underweight (OR 1.24, 95% CI: 1.12-1.37) and lactating (OR 1.11, 95% CI: 0.98-1.24); had three or more children (OR 1.15, 95% CI: 0.98-1.36) reported significantly higher likelihood of being anaemic. Age, education, household wealth, social group, source of drinking water, residence, nutritional status, maternity status was significantly associated with anaemia. Therefore, targeted interventions considering the discussed determinants may help in reducing anaemia.